2010
DOI: 10.1007/s10763-010-9257-9
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Change Texts in Chemistry Teaching: A Study on the Particle Model of Matter

Abstract: This study explores the effect of a conceptual change text on students' awareness of common misconceptions on the particle model of matter. The conceptual change text was designed based on principles of text comprehensibility, of conceptual change instruction and of instructional approaches how to introduce the particle model. It was evaluated in an empirical study with 214 students. Students' learning was measured with a pre-post-test design. Item response theory was used for analysing students' answers. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
(46 reference statements)
3
23
0
10
Order By: Relevance
“…As hypothesized, the conceptual change texts, analogies and animated videos combination did lead to better conceptual understanding of related genetic concepts. These results support the findings of former studies in which text-based conceptual change approach can facilitate learning of scientific concepts (Chambers & Andre, 1997;Hynd, Alvermann, & Qian, 1997;Sungur, Tekkaya & Geban, 2001;Cakir et al, 2002;Alparslan, Tekkaya & Geban, 2003;Pekel, 2005;Pinarbasi et al, 2006;Beerenwinkel et al, 2011), importance of analogies (Stavy, 1991;Dagher 1994;Durkin & Barber, 2002;Canpolat et al, 2006;Çetingül and Geban, 2011) (Beentjes & VanderVoort, 1991;Schnotz, 2002;Wang & Hartley, 2003;Annetta et al, 2009), animations (Annetta et al, 2009;Papastergiou, 2009;Bourgonjon, 2010). In addition, students exposed to conceptual change based instruction had more positive attitudes than the students exposed to traditional instruction.…”
Section: Discussionsupporting
confidence: 87%
“…As hypothesized, the conceptual change texts, analogies and animated videos combination did lead to better conceptual understanding of related genetic concepts. These results support the findings of former studies in which text-based conceptual change approach can facilitate learning of scientific concepts (Chambers & Andre, 1997;Hynd, Alvermann, & Qian, 1997;Sungur, Tekkaya & Geban, 2001;Cakir et al, 2002;Alparslan, Tekkaya & Geban, 2003;Pekel, 2005;Pinarbasi et al, 2006;Beerenwinkel et al, 2011), importance of analogies (Stavy, 1991;Dagher 1994;Durkin & Barber, 2002;Canpolat et al, 2006;Çetingül and Geban, 2011) (Beentjes & VanderVoort, 1991;Schnotz, 2002;Wang & Hartley, 2003;Annetta et al, 2009), animations (Annetta et al, 2009;Papastergiou, 2009;Bourgonjon, 2010). In addition, students exposed to conceptual change based instruction had more positive attitudes than the students exposed to traditional instruction.…”
Section: Discussionsupporting
confidence: 87%
“…Conceptual change texts are "one of the most successful techniques based on [the] conceptual change approach" [68] (p. 240) and represent a methodological means of refuting false single beliefs [69][70][71]. Conceptual change texts are a specific type of text in which a false single belief that the reader may have is first explicitly acknowledged before the corresponding scientific concept is explained [72,73]. According to Egbers and Marohn [74], the reader must write a reflection before and after reading the text in which they take a clear position on a given statement (e.g., a neuromyth).…”
Section: Conceptual Change In Biology Teacher Educationmentioning
confidence: 99%
“…It is also shown that students do not always perceive the difference between matter and energy, that they might not recognize that atoms are everywhere-in all kinds of objects-around us, and that they struggle to understand ''empty space'' between particles. The fact that students often lack sub-microscopic explanations for macroscopic observations of phenomena is also well known, and switching between particle models and observable phenomena can therefore be an overwhelming conceptual demand (Andersson, 1990;Beerenwinkel, Parchman, & Gräsel, 2010;De Jong, Van Driel, & Verloop, 2005;Driver, Guesne, & Tiberghien, 1985;Driver, 1994;Harrison & Treagust, 2002;Krnel, Watson, & Glazar, 1998Renström, Andersson, & Marton, 1990). At the secondary level, students are taught to interpret phenomena in chemistry in terms of particle models and explain them using scientific language, known among science teachers as a difficult task.…”
Section: Introductionmentioning
confidence: 99%